Control of motor units during voluntary force-production: implications for exercise - de Luca, C. J.; Contessa, P.; Nawab, S. H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
We have recently developed a technology that enables studies of the firing properties of a large set (typically 30 to 40) of concurrently active motor units during isometric voluntary contractions ranging from low force levels to maximal voluntary contractions (MVC). With this technology we have executed studies to investigate the behavior of the firing rates of motor units as a function of their recruitment properties during contractions at various force levels. We found that the firing rates have a hierarchical structure wherein the firing rate value of motor units is inversely related to their recruitment threshold, with earlier recruited motor units having greater firing rates at any time and any force level during a contraction. This relationship does not support the opposite notion that has been generally held for the past five decades. Knowing the structure of the firing behavior of motor units during voluntary contractions provides guidance for understanding the performance of muscles during exercise and sports.